Range of Motion Exercise to Improve Muscle Strength among Stroke Patients: A Literature Review - Yanti Srinayanti; Wina Widianti; Dian Andriani; Fidya Anisa Firdaus; Henri Setiawan (Alta Dharma Publisher, 2021)
Stroke was a disturbance in part or all brain function caused by abnormal blood flow to the brain, disrupting bodily functions such as muscle weakness. One of the efforts that could be done to overcome muscle weakness in stroke patients was the Range Of Motion (ROM) exercise which could be done independently or assisted by health workers. The purpose of this literature review was to identify the effect of range of motion (ROM) exercise in increasing muscle strength in stroke patients. This study used a descriptive method with a literature review approach. The search strategy used six international journal databases: PubMed, JSTOR, Wiley Online Library, Sage Journal, ScienceDirect, and Taylor & Francis Online. In addition, a search was conducted on one national journal database, namely Google Scholar. The selection was conducted by assessing articles that met the inclusion criteria, such as publication range from 2005-2021, in English, Indonesian, and other languages that can be translated and opened full access text. After the selection process, nine articles that met the inclusion criteria were obtained, with 197 respondents assigned randomly and grouped into 58 control groups, 55 intervention groups, 84 combined groups. The results showed that the ROM exercise method positively affected increasing muscle strength in stroke patients. Based on these results, it could be concluded that this nurse's independent intervention needed to be carried out in stroke patients to increase muscle strength